Consumer Perception of Online Marketplace in Bangladesh: An Empirical Study on Dhaka City - Khatun, Most. Moriom; Rahamatullah, Noor M; Afrin, Tanjina; Islam, Safiul; Rahman, Mofasser (Asian Business Review, 2020)
Bangladesh is one of the growing economically developing countries, where the online marketplace is becoming popular in recent days. Besides the traditional market or super shops, online marketplaces grab the eyeballs of the consumers, because of avoiding a heavy traffic jam, huge time consuming, public gathering, and recent Covid-19 lockdown. This paper conducted an empirical study to measure the consumer perception of the online marketplace. The relationship between consumer preference and demographic data is also analyzed. It has been found that major responders are young in age, male in gender, and student and jobholders in occupation. Whereas, books and foods are the main preferred product to purchase online because those twos are reliable and easy to ensure quality rather than clothing, cosmetics, and other products. A suggestion would be concluded by this paper is that products in the online marketplace must increase the quality and reliability to ensure the purchasing preference by the consumers.